Stochastic Behavior of Phase Synchronization Index and Cross-Frequency Couplings in Epileptogenic Zones during Interictal Periods Measured with Scalp dEEG - Ramon, Ceon; Holmes, Mark D. (Frontiers in Neurology, 2013)
The stochastic behavior of the phase synchronization index (SI) and cross-frequency couplings on different days during a hospital stay of three epileptic patients was studied for noninvasive localization of the epileptogenic areas from high density, 256-channel, scalp EEG (dEEG) recordings. The study was performed with short-duration (0-180 sec), seizure-free, epileptiform-free and spike-free interictal dEEG data on different days of three subjects. The seizure areas were localized with subdural recordings with an 8×8 macro-electrode grid array and strip electrodes. The study was performed in theta (3-7 Hz), alpha (7-12 Hz), beta (12-30 Hz) and low gamma (30-50 Hz) bands. A detrended fluctuation analysis was used to find the long range temporal correlations in the SI that reveals the stochastic behavior of the SI in a given time period. The phase synchronization was computed after taking Hilbert transform of the EEG data. Contour plots were constructed with 20 sec time-frames using a montage of the layout of 256 electrode positions. It was found that the stochastic behavior of the SI was higher in epileptogenic areas and in nearby areas on different days for each subject. The low gamma band was found to be the best to localize the epileptic sites. Also, a stable higher pattern of SI emerged after 60-120 seconds in the epileptogenic areas. The cross-frequency couplings of SI in theta-gamma, beta-gamma and alpha-gamma bands were decreased and spatial patterns were fragmented in epileptogenic areas. Combinations of an increase in the stochastic behavior of the SI and decrease in cross-frequency couplings are potential markers to assist in localizing epileptogenic areas. These findings suggest that it is possible to localize the epileptogenic areas noninvasively from a short-duration (~ 180 sec), seizure-free and spike-free interictal scalp dEEG recordings.